National Security Systems on The Threat Perception Index - Tobing, Victor; Muradi, Muradi (The Republic of Indonesia Defense University, 2015)
This study focused on five variables threat perception, in the strategic decision making process. This study uses a quantitative approach to threat perception index and analytic hierarchy process method. Threat perception index variables: changes in global power mapping, strategic environment with high ambiguous, the political system in the country, domestic and violations of socio-cultural norms. The results of this research: (1) variable political system in the country, domestic and social culture of critical signals violation of norms derived from the analytic hierarchy process can be used as the basis for establishing the national security system; (2) The threat perception index in international relations